DAMPAK PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) DALAM MENGATASI RENDAHNYA MINAT SAINS SISWA DI SEKOLAH DASAR - Dzahira Shofa, Annisa; Fitria Nurulaeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The integration of science and social studies into science in the Independent Curriculum aims to develop 21st-century skills. This study analyzes the implementation of the Problem-Based Learning (PBL) model predominantly used by teachers, with a focus on the impacts and constraints in five elementary schools in Karangtengah District. Using a qualitative case study approach, data was collected from 39 informants (9 teachers, 30 students) through observation, interviews, and documentation with data triangulation validation. The results revealed that the main constraints included material preparation, classroom management, limited facilities, and time effectiveness. Although 74% of students still struggled with focus, the implementation of PBL proved to have a significant positive impact. There was an increase in conceptual understanding, learning outcomes, critical thinking, and student motivation of up to 100%. Students became more active, independent, and bold in expressing their opinions in solving real-world problems. In conclusion, despite facing technical challenges, the PBL model is effective in shaping student character. To optimize its implementation, ongoing teacher training and adaptive classroom management strategies are needed to overcome obstacles in the field.